CIMUVET-survey: Complementary and Integrative Medicine (CIM) use in veterinary practice in Austria and CIM education at universities in Austria, Germany and Switzerland - Pia Forster; Annemarie Käsbohrer; Holger Cramer; Michael Frass; Ariane Maeschli; David Martin; Peter Panhofer; Birgit Ursula Stetina; Ursula Wolf; Jürgen Zentek; Petra Weiermayer (PLoS ONE, 2025)
Introduction Complementary and Integrative Medicine (CIM) are an important component of healthcare worldwide according to the WHO Traditional Medicine Strategy. The Licensing Regulation for Physicians in Germany and the Medical Professions Act in Switzerland stipulate that CIM must be taught as an integral part of the human (DE, CH) or veterinary (CH) degree programme. The aim of this study was to evaluate the status of CIM in veterinary practice in Austria in context with an overview on practice, research and teaching at the universities of human and veterinary medicine in German speaking countries. Materials and methods Using a cross-sectional study design, an anonymous questionnaire on the use of CIM in veterinary practice was sent out via the Austrian Veterinary Chamber. Chairs, professorships and institutes, and courses on CIM at universities of human and veterinary medicine were researched online. Results Of the 246 voluntary participants, 58.9% reported a positive, 22.4% a negative and 15.4% a neutral attitude towards CIM. Of the livestock veterinarians, 68.9% were familiar with the requirement of the EU Organic Regulation, as were 54.1% of all veterinarians. The integration of CIM into the Vetmeduni Vienna curriculum was rated as very important by 35.8% of participants with at least partial approval by 68.7%. The demand for CIM by patient owners amounted to 83.7% and the use of CIM in animals to 65.9%. At Austrian, German, and Swiss universities, 39 professorships of CIM in human medicine (AT: 2; DE: 32; CH: 5) were identified while in veterinary medicine, seven professorships for animal nutrition and dietetics (AT: 2; DE: 5) were identified. Conclusion Based on the results of the CIMUVET study, integrating CIM as in university curricula and hospitals in Switzerland and Germany is a promising future development for Austria. These approaches should follow the WHO Traditional Medicine Strategy 2025–2034.